STUDI PENERAPAN PRODUKSI BERSIH (STUDI KASUS PADA PERUSAHAAN PULP AND PAPER SERANG) - Nugraha, Winardi Dwi; Susanti, Ina (Universitas Diponegoro, 2006)
Cleaner produktion is minimization of waste from source. That is can do with some way of likes reuse, reclyle, recovery or house keeping. PT. Indah Kiat Pulp and Paper that location in Kragilan Village, Serang Banten is paper mill that in their production aplicated cleaneer production concept. Action that PT. Indah Kiat Pulp and Paper does in aplicated cleaneer production concept is recovery fiber loss from waste water, reuse product fail and house keeping.